Out of the box: Google and the contagion of control. (September 2013) - James, Roger
As Google and other members of the Gang of Four (Apple, Amazon, Facebook and Google) come under fire for their business practices it is worth reviewing progress towards the information nirvana described by the author just two years ago (in Out of the box: Joining the Dots ). In this mid-term report the author develops his doubts about their future because, in 2013, Google turned their back on openness and information fairness. Like Microsoft before them, their strategy crossed from technology led to marketing led. If history repeats its pattern it condemns them to a managerial hubris where legal defence replaces technological determinism. The battle lines are drawn around two little noticed technical changes: the withdrawal of RSS news alert services and the retirement of the synonym operator in search. The first betrays the principle of symmetry essential for information fairness, the second reveals a new master's voice where the needs of marketing replace Information Science as the guide of product development. In response, it is time to start work on the information responsibility of organizations such as Google and to spell out their responsibilities to maintain an RSS neutral impact on our planet of information.